Nils-Øivind Haagensen, "E a ta?" ["Er hun din?"/ "Is She Yours?"], translated from Norwegian by Raluca-Daniela Duinea, Cluj-Napoca: Casa Cărții de Știință, 2023, 232 p. - BOZÎNTAN, Georgiana (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Nils-Øivind Haagensen is a Norwegian poet, writer, journalist and the head of Flamme Publishing House. He debuted as a poet in 1998 with the volume Hender og hukommelse (Hands and Memories) and as a novelist in 2001 with Det radioaktige (The Radioactive). In 2013 he was nominated for Nordisk råds litteraturpris (Nordic Council Literature Prize) for the volume of poetry God morgen og god natt (Good Morning and Good Night, 2012). Among his latest publications are the novels Dette norske livet (This Norwegian Life, 2019) and Sangria i parken (Sangria in the Park, 2021). The novel Er hun din? (Is She Yours?) was published in 2016 at Oktober Publishing House in Norway and in 2023 it was translated into Romanian by Raluca-Daniela Duinea, being Haagensen’s first translation published in Romania at Casa Cărții de Știință Publishing House, the Nordica Collection, in Cluj-Napoca, with financial support from NORLA (Norwegian Literature Abroad).